Developing Communicative Learning Materials for Teaching English as a Foreign Language to Students of Elementary Teacher Study Program of Flores University of East Nusa Tenggara - Ota, Maria K. (Universitas Pendidikan Ganesha, 2018)
This study aimed at developing communicative learning materials for teaching English as a foreign language to students of elementary teacher education study program of Flores University. The instruments used in this study were observation sheet, interview guide, scoring rubric, and questionnaire which were used to gather data during product’s development. This study used the research and development model proposed by Sugiyono (2009). The result shows that the developed communicative learning materials were relevant to the students’ needs. The learning materials which were designed in the form of a textbook were relevant to the students’ expertise and the developed materials which were used along with communicative activities were categorized as having good quality. The implementation of the communicative materials are effectively implemented in the classroom where the result of posttest mean score was 86 and pretest mean score was 75. The lecturers of English in this study program are suggested to use these present communicative learning materials and various activities in order to avoid the boredom of the students during teaching and learning process. The various activities used can help learners to enhance their English abilities in communication and the students’ improvements of English can be increased.